Augmenting Buried in Treasures with in-home uncluttering practice: Pilot study in hoarding disorder. (December 2018) - Linkovski, Omer; Zwerling, Jordana; Cordell, Elisabeth; Sonnenfeld, Danae; Willis, Henry; La Lima, Christopher N.; Baker, Colleen; Ghazzaoui, Rassil; Girson, Robyn; Sanchez, Catherine; Wright, Brianna; Alford, Mason; et al.
Abstract: Hoarding disorder is characterized by difficulty parting with possessions and by clutter that impairs the functionality of living spaces. Cognitive behavioral therapy conducted by a therapist (individual or in a group) for hoarding symptoms has shown promise. For those who cannot afford or access the services of a therapist, one alternative is an evidence-based, highly structured, short-term, skills-based group using CBT principles but led by non-professional facilitators (the Buried in Treasures [BIT] Workshop). BIT has achieved improvement rates similar to those of psychologist-led CBT. Regardless of modality, however, clinically relevant symptoms remain after treatment, and new approaches to augment existing treatments are needed. Based on two recent studies - one reporting that personalized care and accountability made treatments more acceptable to individuals with hoarding disorder and another reporting that greater number of home sessions were associated with better clinical outcomes, we tested the feasibility and effectiveness of adding personalized, in-home uncluttering sessions to the final weeks of BIT. Participants (n = 5) had 15 sessions of BIT and up to 20 hours of in-home uncluttering. Reductions in hoarding symptoms, clutter, and impairment of daily activities were observed. Treatment response rate was comparable to rates in other BIT studies, with continued improvement in clutter level after in-home uncluttering sessions. This small study suggests that adding in-home uncluttering sessions to BIT is feasible and effective. Highlights: In-home uncluttering sessions augment evidence-based hoarding treatment (BIT). Augmented BIT improved overall hoarding symptoms, clutter, and functioning. Study procedures were feasible and well tolerated by study participants.